2022
DOI: 10.1177/14713012221084173
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-home participation among people living with dementia: A study in four countries

Abstract: Social participation in out-of-home activities is important for people living with dementia, yet little is known about such participation. The aim of this study was to explore and compare out-of-home participation among people living with dementia in four countries by assessing different types of places of participation visited or no longer visited. A cross-sectional design was used to gather self-reported experiences concerning out-of-home participation among people with mild stage dementia living in Canada (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…In one multicentric, multimethod study conducted between 2015 and 2017, public transportation service was granted for 33% of participants with mild-stage dementia in Canada, 74% in Sweden, and 11% in Switzerland ( Thalén et al, 2022 ). Sweden had a significantly higher rate of granted public transportation service than the others, whereas Switzerland had a significantly lower rate ( p < .001, with post-hoc tests with Bonferroni correction).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one multicentric, multimethod study conducted between 2015 and 2017, public transportation service was granted for 33% of participants with mild-stage dementia in Canada, 74% in Sweden, and 11% in Switzerland ( Thalén et al, 2022 ). Sweden had a significantly higher rate of granted public transportation service than the others, whereas Switzerland had a significantly lower rate ( p < .001, with post-hoc tests with Bonferroni correction).…”
Section: Resultsmentioning
confidence: 99%
“…For example, urban transportation systems may be well developed and available, but there were challenges in the large interchanges for people living with dementia ( Innes et al, 2016 ); rural spaces may have more individualized transportation, but the service availability was inconsistent and required higher cost ( Silverstein & Turk, 2016 ). In urban areas, access to a larger public transportation system such as rail and bus systems could be surveyed ( Thalén et al, 2022 ). In rural areas, paratransit and door-to-door services by volunteers and paid drivers were generally described ( Dobbs et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…For these individuals, maintaining the status quo of independent living, comprising both domestic and social autonomy, is of high value [4,5]. However, the reality of the practical and emotional challenges of living with dementia, such as difficulties with direction or the perceived stigma of a dementia diagnosis, likely translates into a decline in the propensity for out-of-home social engagement [6]. Hackett et al (2019) found that the percentage of those with cognitive impairment and regular social interactions decreased from 55% pre-diagnosis to 23% post-diagnosis compared to 85% for those with no cognitive impairment [7].…”
Section: Introductionmentioning
confidence: 99%